Aggressive angiomyxoma of the vagina: a case report - Matheo Augusto M. Stumpf; Rebecca S. M. Stival; Alexandre B. Merlini; Fábio P. Mansani; Janicelli B. C. H. Silvestre; Isabela B. Mongruel; Mário R. Montemór Netto
ABSTRACT Aggressive angiomyxoma (AAM) is a rare infiltrative tumor of mesenchymal origin that has high rates of local recurrence. We present the case of a 42-year-old patient with a lump in the vaginal canal, treated with excisional biopsy. Histopathologic evaluation revealed myxoid spindle-cell proliferation in the subepithelial region, and immunohistochemical analysis was positive for CDK4, CD34, desmin, estrogen and progesterone receptors. The markers S100 and smooth muscle actin were negative, what corroborated the diagnosis of AAM. Because of its high recurrence rates, we opted for outpatient follow-up during the two subsequent years.